32 Lessons for the Development of Cognitive Skills and Metacognitive Skills in 8 Year-old Children - Z. Zak, Anatoly (International Journal of Psychosocial Rehabilitation, 2020)
The following skills were examined: cognitive skills (combinatorial skills, logical skills related to reasoning and comparison, planning skills for problem-solving) and metacognitive skills related to reflection on problem-solving methods. The purpose of the study was to determine the conditions for the development of the above-mentioned skills in 8-year-old children. The assumption was that the “Intellectica” original educational program establishes such conditions. The program includes 32 types of non-standard problems with non-curricular content: 9 narrative-logical problems, 6 comparative problems (comparisons of schematic object representations), 8 spatial problems, 9 route problems (that involve movement of imaginary characters according to specific rules). Each problem type had three structural versions of tasks: find an answer, find the question, find a part of the initial conditions. The control group consisted of 127 children; the experimental group contained 131 children. These children participated in 32 group lessons (weekly, September through May). Initial and final diagnostics of the above-mentioned skills were held in the experimental and control groups. Comparison of results indicates that the children in the experimental group demonstrate significantly higher results than the children in the control group. The study showed that “Intellectica” lessons contribute to the development of the above-mentioned skills in children. In further studies it is planned to determine to what extent the "Intellectica" program promotes the development of the above-mentioned skills of 9-year-old children.